2007
DOI: 10.1002/ibd.20017
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal elimination of TNF-α-producing CD14dullCD16+ monocytes in leukocytapheresis therapy for ulcerative colitis

Abstract: The present findings revealed the real target of proinflammatory CD14(dull)CD16(+) monocytes removed during LCAP treatment of UC and that LCAP might be used as an extracorporeal anti-TNF-alpha therapy, expanding the clinical applications of this procedure to include the treatment of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…[21][22][23] Furthermore, patients who develop pouchitis show higher activation of signal transducer and activator of transcription (STAT)-1, a transcription factor that activates genes involved in infl ammatory and immune responses, in the pouch mucosa. 24 LCAP may reduce infl ammation via the removal of activated leukocytes that produce infl ammatory cytokines such as interleukin (IL)-1, IL-6, and TNF-α, [25][26][27] and the removal of activated platelets that can produce active oxygen. [28][29][30] Standard medical therapy for pouchitis attempts to interfere with luminal bacteria using antibiotics or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Furthermore, patients who develop pouchitis show higher activation of signal transducer and activator of transcription (STAT)-1, a transcription factor that activates genes involved in infl ammatory and immune responses, in the pouch mucosa. 24 LCAP may reduce infl ammation via the removal of activated leukocytes that produce infl ammatory cytokines such as interleukin (IL)-1, IL-6, and TNF-α, [25][26][27] and the removal of activated platelets that can produce active oxygen. [28][29][30] Standard medical therapy for pouchitis attempts to interfere with luminal bacteria using antibiotics or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanisms including the triggering of immunomodulatory or regulatory processes have been suggested to be operative [3,4,[15][16][17][18]. Moreover, the release of biologically active substances from the cells adsorbed in the apheresis columns has also been described [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…LCAP treatment is considered to exert its effects against inflammatory diseases by influencing the cytokine balance through adsorption and removal of activated leukocytes, and causing functional changes of inflammatory cells [8] . In particular, Kanai et al [7] reported that the real target of pro-inflammatory monocytes was removed during LCAP treatment of ulcerative colitis. The present study produced the same results as these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, activated monocytes/macrophages have an important role in the pathogenesis of HPS. In recent years leukocytapheresis using a leukocyte removal filter (known as lymphocytapheresis, LCAP) has been applied to the treatment of various autoimmune diseases [7] . The removal of activated monocytes during LCAP treatment appears useful for hypercytokinemia [8] .…”
Section: Introductionmentioning
confidence: 99%